Incidence and correlates of receiving cigarettes as gifts and selecting preferred brand because it was gifted: Findings from the ITC China Survey - Huang Li-Ling; Thrasher James F; Jiang Yuan; Li Qiang; Fong Geoffrey T; Quah Anne CK (BMC, 2012)
Abstract Background Giving cigarettes as gifts is a common practice in China, but there have been few systematic studies of this practice. The present study was designed to estimate the incidence of receiving cigarettes as gifts, correlates of this practice, and its impact on brand selection in a representative sample of urban adult smokers in China. Methods Data were analyzed from Wave 2 of the International Tobacco Control (ITC) China Survey, where 4843 adult urban smokers were interviewed in six major Chinese cities between October 2007 and January 2008. The incidence of most recent cigarette acquisition due to gifting and the prevalence of preferred brand selection due to having received it as a gift were estimated. Bivariate and adjusted logistic regression models were estimated to identify factors associated with these two outcomes. Results The incidence of receiving cigarettes as a gift at most recent cigarette acquisition was 3.5%. Smokers who received these gifted cigarettes were more likely to be female, older, have higher educational attainment, live in Beijing, and smoke fewer cigarettes per day. The prevalence of choosing one's preferred brand due to having received it as a gift was 7.0%, and this was more likely among smokers who lived in Beijing and Guangzhou, had lower educational attainment, smoked less frequently, and had smoked their preferred brand for less than one year. Conclusions The 3.5% incidence of one's most recent cigarette acquisition due to gifting is consistent with prevalence estimates based on longer reference periods and translates into the average smoker receiving a gift of cigarettes approximately five times a year. Gifting also appears to have a significant influence on brand preference. Tobacco control interventions in China may need to denormalize the practice of giving cigarettes as gifts in order to decrease the social acceptability of smoking.